2013
DOI: 10.1021/ja408422y
|View full text |Cite
|
Sign up to set email alerts
|

Control of Mode/Bond Selectivity and Product Energy Disposal by the Transition State: X + H2O (X = H, F, O(3P), and Cl) Reactions

Abstract: The ability to predict mode/bond selectivity and energy disposal is of central importance for controlling chemical reactions. We argue that the transition state plays a critical role in state-to-state reactivity and propose a simple sudden model based on coupling with the reaction coordinate at the transition state. The applicability of this so-called sudden vector projection (SVP) model is examined for several prototypical atom-triatom, namely, X + H2O (X = H, F, O((3)P), and Cl) reactions. It is shown that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
154
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 128 publications
(166 citation statements)
references
References 88 publications
11
154
0
Order By: Relevance
“…On the other hand, fulldimensional quantum models have currently been amenable to the four-atom reactions and such studies have shown that the symmetric and antisymmetric stretching modes of H 2 O have large and nearly equal efficacies in promoting its reactions with H and Cl. [22][23][24][25][26][27] Contrast to CH 4 , however, the stretching modes of H 2 O are singly degenerate. As a result, the observation in the H/Cl + H 2 O reactions does not necessarily help to shed light on the relative efficacies of the two stretching modes in the H/Cl + CH 4 reactions.…”
mentioning
confidence: 99%
“…On the other hand, fulldimensional quantum models have currently been amenable to the four-atom reactions and such studies have shown that the symmetric and antisymmetric stretching modes of H 2 O have large and nearly equal efficacies in promoting its reactions with H and Cl. [22][23][24][25][26][27] Contrast to CH 4 , however, the stretching modes of H 2 O are singly degenerate. As a result, the observation in the H/Cl + H 2 O reactions does not necessarily help to shed light on the relative efficacies of the two stretching modes in the H/Cl + CH 4 reactions.…”
mentioning
confidence: 99%
“…The quantum dynamics were represented in Jacobi coordinates (shown in Fig. 1) by a 6D Chebyshev real wave-packet method (20,35). Specifically, an initial wave packet was launched for a rovibrational state of reactant (D 2 O) above the surface and propagated on the PES using the Chebyshev three-term recursion formula.…”
mentioning
confidence: 99%
“…The vibrational enhancement of the reactivity can be understood by the recently proposed sudden vector projection (SVP) model, which assumes that the reaction occurs in the sudden limit, and the enhancement of reactivity by a reactant mode reflects its coupling with the reaction coordinate at the transition state (35,44). Such coupling can be estimated by the projection of the reactant mode vector onto the reaction coordinate vector at the transition state.…”
mentioning
confidence: 99%
“…In this regard, the propensity toward translational energy at low collision energies can also be found in many other activated reactions. [29][30][31][35][36][37][38][39][40][41][42][43][44] On intuitive grounds, a finite momentum of the two reactants seems necessary in order to drive reactions over barriers. If correct, a translational propensity in the post-threshold region of activated reactions may well be a general trait; regardless it is an early-, central-, or late-barrier reaction.…”
mentioning
confidence: 99%